Long‐term discontinuation of warfarin in a patient with HeartMate 3 left ventricular assist device without complication. Issue 2 (15th November 2019) - Fiedler, Amy G.; Hermsen, Joshua L.; Smith, Jason W.; Dhingra, Ravi
Abstract: A 38‐year‐old woman with peripartum cardiomyopathy underwent placement of a HeartMate 3 (HM3) left ventricular assist device (LVAD). Postoperatively, she refused warfarin therapy and was maintained on aspirin monotherapy for 19 months. She did not experience thrombotic or thromboembolic complications associated with lack of oral vitamin K antagonist anticoagulation. Our patient represents the longest reported duration of a patient with HM3 LVAD maintained without warfarin without evidence of thrombotic or thromboembolic events.